Fresh and Hardened properties of Self-Compacting Concrete Containing Different Mineral Admixtures - T, Chiranjeevi; Chandrasekhar Rao .T, Dr.; ., . (International Journal of Engineering and Technology, 2018)
Self-Compacting Concrete is an innovative concrete that does not require vibration for placing and compaction. It is able to flow under its own weight, completely filling formwork and achieving full compaction, even in the presence of congested reinforcement. This paper presents an experimental investigation on strength aspects like compressive, flexural and split tensile strength of self compacting concrete containing different mineral admixtures and workability tests for different mineral admixtures are carried out. The methodology adopted is that mineral admixtures are replaced by 30%, 40% and 50% for Portland cement and performance is measured and compared. The influence of mineral admixtures on the workability, compressive strength, splitting tensile strength and flexural strength of self-compacting concrete was investigated. The mix proportion is obtained as per the guidelines given by European Federation of producers and contractors of special products for structure. The following inferences were made; optimum dosage of super plasticizer enhanced the flow property of the concrete. As a result, overall improvements in the flow and filling ability of the self-compacting concrete were observed. It is observed that when mineral admixtures used in self-compacting concrete, can reduce the amount of super- plasticizer necessary to achieve a given fluidity. It should be noted that the effect of mineral admixtures on admixture requirements is significantly dependent on their particle size distribution as well as particle shape and surface characteristics. From this view point, a cost effective self-compacting concrete design can be obtained by incorporating reasonable amounts of silica fume, fly ash, and ground granulated blast furnace slag.Â Â